2022
DOI: 10.3390/land11050708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Forest Tenure Reform on Farmers’ Investment in Public Welfare Forest Areas: A Case Study of Gansu Province, China

Abstract: In recent times, forest tenure reform has become one of the most discussed agendas among local and global policymakers. Forest tenure is a contract that specifies who has rights to forestry resources and depicts who should utilize, maintain, and acquire them. It can have a significant impact on whether farmers invest in their forestland. The study’s primary purpose is to explore whether and how the reform of forest rights affects farmers’ investment in public welfare forestry. More specifically, the study thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…If the forest logging restriction is tightened, it will be more challenging for rural households who plant timber forests to reach their harvesting goals. If rural households' timber forests are classified as public welfare forests in the future, harvesting will be entirely prohibited and their losses will increase [29]. To avoid risk, rational rural households will convert their extant timber forests into economic forests [30].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…If the forest logging restriction is tightened, it will be more challenging for rural households who plant timber forests to reach their harvesting goals. If rural households' timber forests are classified as public welfare forests in the future, harvesting will be entirely prohibited and their losses will increase [29]. To avoid risk, rational rural households will convert their extant timber forests into economic forests [30].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Lin et al (2020), based on empirical research using household data from 18 counties in China, indicated that the CFTR positively impacted forestry management investment [10]. On the other hand, some scholars, using empirical research from household surveys, have shown that the CFTR can increase households' input of production factors in the short term, but this effect gradually weakens over time [11,12]. Xie et al (2016), using instrumental variable methods to control for factors other than the CFTR, examined the impact of the CFTR on afforestation, finding that the CFTR significantly increased the afforestation area by 7.68% in the same year, but the effect disappeared in subsequent years [13].…”
Section: Introductionmentioning
confidence: 99%
“…One study discovered an investment incentive effect by comparing rural household forestry investments before and after the collective forestland tenure reform [16]. In the short run, the principal reform of forestland tenure can increase rural households' investment intensity [17]. It can be seen that collective forestland tenure reform can effectively reduce the information cost due to transaction information asymmetry and promote the development of forestland tenure flow market, thus affecting the allocation structure of forestry production factors.…”
Section: Introductionmentioning
confidence: 99%